Teaching English for Students with Special Educational Needs During the Pandemic - Ridzig, Gabriella; Hrabéczy, Anett; Hegedűs, Gabriella (Central European Journal of Educational Research, 2024)
This research aimed to examine the impact of distance learning on SEN students’ English language education, parental involvement in the education of these children, as well as the ICT tools used for their development. There is little information about the difficulties and trials these students and their teachers had to face during the COVID-19 epidemic. Moreover, parental involvement plays a significant role in school performance, but there is little information about how this was realized during distance learning. We assumed that the biggest problem was the transition from face-to-face education to the online sphere. To examine this, we conducted semistructured personal interviews with elementary school English teachers from north-eastern Hungary. The most important result of our research is that during this period only a few SEN students could receive special, individual lessons, and differentiated education was implemented to a somewhat limited extent. To conclude, more programs should be created that meet the different needs of SEN to properly educate these children, and that as many development specialists as possible, who could provide group or individual lessons, should be recruited.